2006
DOI: 10.1088/1126-6708/2006/01/094
|View full text |Cite
|
Sign up to set email alerts
|

AdS3solutions of IIB supergravity from D3-branes

Abstract: We consider pure D3-brane configurations of IIB string theory which lead to supersymmetric solutions containing an AdS 3 factor. They can provide new examples of AdS 3 /CFT 2 examples on D3-branes whose worldvolume is partially compactified. When the internal 7 dimensional space is non-compact, they can be identified as supersymmetric fluctuations of higher dimensional AdS solutions and are in general dual to 1/8-BPS operators thereof. We find that supersymmetry requires the 7 dimensional space take the form o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
342
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(362 citation statements)
references
References 24 publications
19
342
0
1
Order By: Relevance
“…A double Wick rotated version of this system (i.e. one with AdS 3 instead of S 3 isometry) was recently investigated in [20], and the results are directly applicable to the present case. The analysis of [20] demonstrated that the seven-dimensional metric may be written as time fibered over a six (real) dimensional Kähler base which satisfies an appropriate geometric condition.…”
Section: /8 Bps Configurationsmentioning
confidence: 93%
See 4 more Smart Citations
“…A double Wick rotated version of this system (i.e. one with AdS 3 instead of S 3 isometry) was recently investigated in [20], and the results are directly applicable to the present case. The analysis of [20] demonstrated that the seven-dimensional metric may be written as time fibered over a six (real) dimensional Kähler base which satisfies an appropriate geometric condition.…”
Section: /8 Bps Configurationsmentioning
confidence: 93%
“…Backgrounds with S 3 × S 1 isometry were initially examined in [18], and subsequent gauging of the U(1) isometry was considered in [19]. In addition, solutions preserving an S 3 isometry (corresponding to the 1/8 BPS case) may be obtained by double analytic continuation of the AdS 3 solutions investigated in [20], as it was later done in [21]. (Note that 1/4 BPS and 1/8 BPS solutions of a different nature were also investigated in [4] and [22], respectively.)…”
Section: Jhep10(2007)003mentioning
confidence: 99%
See 3 more Smart Citations